A Multicenter Randomized Double-Blind Vehicle-Controlled Parallel Group Phase 2 Study Evaluating the Efficacy and Safety of GN-037 Cream in Patients with Mild-to-Moderate Plaque Psoriasis - Burhan Engin; Müge Güler Özden; Özge Sevil Karstarlı Bakay; Selda Pelin Kartal; İlkin Zindancı; Salih Levent Çınar; Recep Dursun; Gizem Pehlivan Ulutaş; Tuğba Özkök Özkök Akbulut; Fatma Aslı Hapa; Emel Bülbül Başkan; Mehmet Melikoğlu; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction Topical therapies are used in almost all patients with psoriasis. A novel fixed topical combination cream (GN-037) with a lower concentration (0.0356%) of clobetasol 17-propionate (CP) was developed together with urea, salicylic acid, and retinoic acid to provide a better benefit-risk ratio. The present multicenter randomized double-blind vehicle-controlled parallel group phase 2 study aimed to investigate the efficacy and safety of GN-037 in patients with mild-to-moderate plaque psoriasis (MMPP). Methods Patients (n = 190) were randomized (2:2:1) to receive GN-037 or CP or vehicle (V) cream twice daily to a selected target body lesion for 4 weeks. The primary endpoint was treatment success defined as percentage of patients with at least two-grade improvement in Investigator's Global Assessment Score (IGA) and IGA score equal to 0 or 1 evaluated at weeks 2, 4, 6, and 8 in each arm compared with baseline. Treatment-emergent adverse events (TEAEs) and safety were evaluated throughout the study. Results GN-037 demonstrated statistically significant superiority over V throughout the study. At week 4, treatment success was achieved in 37.9% of patients in the GN-037 arm compared with 29.2% and 9.1% in the CP and V arms, respectively. At least two-grade improvement compared with baseline was achieved by 57.6%, 72.7%, and 80.3% of the patients in the GN-037 arm for erythema, plaque elevation, and scaling, respectively. The mean changes in affected BSA were −2.1 ± 2.9, −1.8 ± 2.4, and −0.5 ± 1.6 in the GN-037, CP, and V arms, respectively. The TEAEs were similar among the arms and the most frequently observed TEAEs were Psoriasis Area and Severity Index (PASI) increase in all arms. Conclusions GN-037 was more effective than V in achieving primary and all secondary endpoints throughout the study. Safety data did not reveal any new safety concerns with the combination cream product. Therefore, 4 weeks of GN-037 treatment demonstrated an excellent efficacy and safety profile in patients with MMPP. Trial Registration number ClinicalTrials.gov identifier, NCT05706870.